Optical Properties of Sodium-doped Carbon Dots Made of Urea and Trisodium Citrate - Isnaeni Isnaeni; Vivi Purwandari; Permono Adi Putro; Hammam Magma Adiwidya (TIME in Physics, 2023)
Carbon dots are very interesting carbon-based nanoparticles. Carbon dots have unique optical properties, especially luminescence properties upon light excitation. Improving optical quality is the challenge in carbon dots research. Doping is one of the methods to improve the quality of carbon dots. In this work, we used sodium, which is an active ion, as doping in the carbon dots. We studied the optical properties of sodium-doped carbon dots. We found that absorbance, FTIR, and photoluminescence spectra changed due additional surface energy level of carbon dots. Furthermore, the quantum yield of carbon dots improved significantly due to sodium doping. In addition, the phosphorescence of sodium-doped carbon dots was slightly longer. Electron behavior was also changed. In conclusion, sodium-doped carbon dots showed very good optical properties for further applications.